Access to Pain Management Programs: A Multifactorial Analysis of the Pathways of Care for Chronic Pain Patients in the University Clinic Erlangen - Dorscht, Lisa; Schön, Christoph; Geiss, Christa; Grässel, Elmar; Donath, Carolin (Gesundheitswesen, 2019)
BACKGROUND: Different treatment options are offered for patients suffering from chronic pain, which differ in intensity and costs: 1) monodisciplinary treatment, mostly in outpatient care and 2) interdisciplinary treatment with the option of participating in pain management programs as outpatients or inpatients. The present work investigates how patients at the University Clinic Erlangen receiving monodisciplinary treatment differ from those receiving interdisciplinary treatment (research question I) as well as how patients participating in a pain management program differ from those who do not (research question II). The aim is to generate insights into whether the differences between the patient groups under various treatment modalities reflect the officially defined criteria for the indication of chronic pain management programs. METHODS: Routine data of 1,833 patients treated from January 2008 to March 2013 at the University Clinic Erlangen were analyzed. After univariate preanalyses and checks for multicollinearity, the remaining variables were used for the final multivariate model (multiple binary logistic regression) for research question I and II. RESULTS: Research question I: Patients getting interdisciplinary treatment were more often employed, had higher affective experience of pain, more often regarded their pain as treatable, had more often participated in at least one pain-associated rehabilitation treatment in the past, were younger and rarely had application for retirement in consideration. Research question II: Patients who participated in a pain management program were more often female, more often employed, described their pain as mainly located at the upper part of the body, had more concomitant symptoms, were more often diagnosed with musculoskeletal pain and rarely had a retirement request pending. CONCLUSIONS: It could be shown that patients in the analyzed pathways of care mainly differed in demographic variables, and regarding pain management programs, also in the type of pain. Differences between patients in different treatment paths reflecting the officially defined indication criteria for chronic pain management programs were detectable only to a minor extent. Clearer and operational practical guidance should help support the clinical decision to assign patients to different treatment options and close the gap between theory and practice.
EVALuna2:215099

A complex intervention to reduce hospital admissions for people living with dementia in shared-housing arrangements in Germany: results of the multicenter, cluster-randomized controlled DemWG-study - Misonow, Julia; Wolf-Ostermann, Karin; Altona, Janissa; Schmidt, Annika; Stiefler, Susanne; Guenay, Serhat; Kratzer, André; Keck, Antonia; Donath, Carolin; Grässel, Elmar (BMC Medicine, 2025)
Background: People living with dementia (PlwD) have a 1.4 times higher risk of hospitalization than people living without dementia. Hospital admissions lead to negative consequences for PlwD and people living with mild cognitive impairment (PlwMCI). Housing models such as shared-housing arrangements (SHAs), which are predominantly used by PlwD, enable care-dependent people to experience daily life as ordinary as possible. However, studies are needed to show how complex non-pharmacological interventions affect hospital admissions, especially in the SHAs setting. Methods: The longitudinal, multicenter, cluster-randomized, controlled, and prospective mixed methods study from April 1, 2019, to December 31, 2022, was part of the German DemWG study and included a waitlist control group design. The multicomponent complex intervention consisted of (a) education of nursing staff in the SHAs—at the beginning of the study, (b) digital education of general practitioners—at the beginning of the study, and (c) the multimodal, psychosocial group intervention MAKS-mk + —structured application of MAKS-mk + between t0 (baseline) and t1 (after 6 months). Longitudinal data were collected at three survey times t0-t2 (t2 at another 6 months follow-up). The primary outcome parameter—hospital admission—was assessed using the nursing documentation. Poisson-models with hierarchical random effects were used for statistical analysis. Results: Nationwide, 97 SHAs with 341 residents participated at t0. Within the longitudinal observation period (12 months, t0-t2), data from 236 participants at t1 and 168 participants at t2 with mild cognitive impairment or mild to moderate dementia were evaluated. In the intention-to-treat sample, the adjusted Poisson-model showed that participants in the intervention group (IG, n = 201) had a significantly lower number of hospital admissions at t1 than participants in the control group (CG, n = 140) (p-value = 0.048; CI = 0.22; 0.99). Beyond t1—“open phase” of the study, no further statistically significant long-term effects of the IG could be identified (p-value ≤ 0.498; CI = 0.25; 1.98). Conclusions: The complex intervention significantly reduced the number of hospital admissions for PlwD and PlwMCI in the “structured phase” of DemWG. This leads to significant improvements in the nursing care and living situation for PlwD and PlwMCI. Since the intervention has been proven to have positive effects and can be easily integrated into SHAs, regular and nationwide integration into everyday care should be given greater consideration. Trial registration: ISRCTN89825211 (Registered prospectively, 16 July 2019).
CRIS-Team Scopus Importer:2025-05-16
Keywords: Cognitive dysfunction; Complex intervention; Dementia; Hospitalization; Housing for the elderly; Psychosocial intervention; Randomized controlled trial; Shared-housing arrangements

Agitation and aggression in people living with dementia and mild cognitive impairment in shared-housing arrangements – validation of a German version of the Cohen-Mansfield Agitation Inventory-Short Form (CMAI-SF) - Kratzer, André; Scheel-Barteit, Jennifer; Altona, Janissa; Wolf-Ostermann, Karin; Grässel, Elmar; Donath, Carolin (Health and Quality of Life Outcomes, 2023)
Background: The Cohen-Mansfield Agitation Inventory-Short Form (CMAI-SF) is a 14-item scale for assessing agitation and aggression, derived from the original 29-item CMAI, and completed by a proxy. Because the CMAI-SF has not yet been validated in German language, the aim of this study is to explore its construct validity. Methods: Baseline data from a cluster-randomized trial to evaluate a non-pharmacological complex intervention for people living with dementia (PlwD) and mild cognitive impairment (MCI) were analyzed. The study sample consisted of 97 shared-housing arrangements (SHAs) in Germany, comprising N = 341 residents with mild to severe dementia and MCI. Trained nursing staff collected data by proxy-rating the CMAI-SF, Neuropsychiatric Inventory-Nursing Home Version (NPI-NH), and QUALIDEM. They also conducted the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Results: In an exploratory factor analysis, three factors emerged: “aggressive behavior”, “verbally agitated behavior”, and “physically non-aggressive behavior”. The CMAI-SF total score showed good internal consistency (α =.85), and the factors themselves showed adequate internal consistency (α =.75/.76/.73). The CMAI-SF showed convergent validity with the NPI-NH agitation item (r =.66) and the NPI-NH “agitation & restless behavior” factor (r =.82). Discriminant validity was confirmed by a low (r =.28) correlation with the NPI-NH apathy item. Quality of life decreased significantly with agitation, as the CMAI-SF showed a moderate negative correlation with the QUALIDEM total score (r = -.35). Conclusions: The 14-item CMAI-SF is a time-efficient, reliable, and valid assessment instrument. Three factors emerged that were similar to those already found in nursing home samples for the original CMAI and the CMAI-SF and in day care samples for the CMAI-SF. The findings provide preliminary evidence that the CMAI-SF can be used instead of the CMAI to reduce time, costs, and burden in future trials. Trial registration: The DemWG study from which data were used to draft this manuscript was prospectively registered on 16 July 2019 at ISRCTN registry (ISRCTN89825211).
CRIS-Team Scopus Importer:2023-06-09
Keywords: Aggression; Agitation; CMAI; CMAI-SF; Cohen-Mansfield Agitation Inventory; Dementia; Mild cognitive impairment; Reliability; Shared-housing arrangements; Validity

Can brief telephone interventions reduce caregiver burden and depression in caregivers of people with cognitive impairment? - Long-term results of the German day-care study (RCT) - Donath, Carolin; Luttenberger, Katharina; Grässel, Elmar; Scheel, Jennifer Felicia; Pendergrass, Anna; Behrndt, Elisa-Marie (BMC Geriatrics, 2019)
Background: Day-care and telephone counseling have been discussed as effective support measures for caregivers of people with cognitive impairment. Methods: In a two-arm cluster-randomized trial involving multicomponent therapy for cognitively impaired persons in day-care centers and telephone counseling for their caregivers versus treatment as usual (TAU), we investigated long-term effects on caregivers' burden and depressiveness. Person-caregiver dyads involving home-dwelling persons with MCI, mild dementia, or moderate dementia were eligible. Day-care centers were randomized into an intervention group (IG) or a control group (CG). Outcome assessors were blinded. Out of 359 caregivers who had completed a 6-month intervention phase (nIG = 205, nCG = 154), a total of 304 of them were available at the 12-month follow-up (nIG = 173, nCG = 131). Instruments for assessing were the Burden Scale for Family Caregivers - short version (BSFC-s) (caregiver burden) and the Well-Being Index Score (WHO-5) (depressiveness). Mixed ANOVAs were used for the main analyses; descriptive statistics and subgroup analyses were additionally performed; secondary analyses involved multiple linear regressions for the main outcomes that were significant in the unadjusted main analysis. Results: At follow-up, crude mean differences showed a nonsignificant advantage for the IG in caregiver burden [IG: -.20 (SD = 5.39) vs. CG:.76 (SD = 5.49), p =.126, d =.177] and depressiveness (reverse scored) [IG: -.05 (SD = 5.17) vs. CG: -.98 (SD = 5.65), p =.136, d =.173]. For caregiver burden, a mixed ANOVA resulted in significant main effects of group (F (1, 302) = 4.40; p =.037) and time (F (1.88, 568.96) = 3.56; p =.032) but not a significant interaction. The largest effects were found for the "mild dementia" subgroup (d =.443 for caregiver burden and d =.520 for depressiveness). Discussion: Positive long-term effects of a combined intervention involving telephone counseling for caregivers and multicomponent activation for patients were observed especially for mild dementia. However, the treatment effects washed out after the intervention ended. Trial registration: ISRCTN16412551 (date: 30 July 2014, retrospectively).
CRIS-Team Scopus Importer:2019-08-06
Keywords: Day-care; Dementia; MCI; Informal caregivers; Telephone intervention

Chronic headache patients’ health behavior and health service use 12 months after interdisciplinary treatment – what do they keep in their daily routines? - Donath, Carolin; Luttenberger, Katharina; Geiss, Christa; Albert, Patricia; Fraunberger, Britta (BMC Neurology, 2022)
Background: We do not yet know whether or the extent to which multimodal therapy changes the health behaviors and health service use of chronic headache patients in the long term. Associations are expected between pain symptoms and pain management abilities for patients who are categorized as successfully treated and those who remain unchanged. Methods: Routine longitudinal data of an enrolment period of five years from 101 headache patients treated with a two-week, full-day, semi-inpatient multimodal pain therapy at the Interdisciplinary Pain Center of the University Clinic Erlangen were available when therapy began and 12 months after treatment. To investigate long-term changes in health behavior and health service use as well as their associations with the outcome “reduction in pain days,” we used descriptive and inferential statistics (i.e., binary logistic regression). Results: Patients who underwent interdisciplinary treatment showed statistically significant changes in their health behavior in five areas. Twelve months after treatment, we found a significantly higher frequency of engagement in athletic sports (p <.001) as well as increases in the use of relaxation techniques (p <.001), TENS devices for relaxation purposes (p =.008), psychological coping strategies (p <.001), and mindfulness-based techniques for dealing with pain (p <.001). 52.8% of the sample reported a reduction in the number of pain days 12 months after treatment. Binary logistic regression (χ2 (12) = 21.419; p =.045; R2 =.255) revealed that a reduction in pain days 12 months after treatment was positively associated with regular physical activity in the form of muscle strengthening and stretching (athletic sports) (p =.012). Conclusion: Chronic headache patients acquired long-term skills from an interdisciplinary treatment concerning the use of relaxation techniques, the use of psychological coping strategies, and physical activity in the form of athletic exercise. Of those, regular athletic exercise was positively associated with a smaller number of pain days in the long term. Thus, a physical activity module should be an element of interdisciplinary treatment for chronic headache patients.
CRIS-Team Scopus Importer:2022-05-06
Keywords: (MeSH): Headache – Headache Disorders; Health Care – Health Services Research; Health Care – Patient-Reported-Outcome Measures – Patient Outcome Assessment – Quality Assurance; Primary – Headache Disorders – Pain Management – Quality Indicators

Compatibility of Work and Family Life of Employees in the Healthcare Sector: An Issue in Health Services Research - Lukasczik, Matthias; Ahnert, Jutta; Stroebl, Veronika; Vogel, Heiner; Donath, Carolin; Enger, Ilka; Grässel, Elmar; Heyelmann, Lena; Lux, Heidemarie; Maurer, Jochen; Özbe, Dominik; Spieckenbaum, Stefanie; et al. (Gesundheitswesen, 2018)
BACKGROUND: Healthcare professionals are confronted with specific work-related demands that influence work-family relations and might indirectly affect the quality of healthcare. This paper seeks to provide an overview of the current state of research on this topic of relevance to health services research. The overview may serve as a starting point for modifying structures in the healthcare system (especially in rural regions) with the aim of improving work-family compatibility. METHODS: A systematic national and international literature search was conducted in terms of a scoping review. The following criteria/contents to be covered in publications were defined: work-family compatibility; work-family interface and work-family conflict in employees working in healthcare; healthcare professions in rural areas and links with work-family issues; interventions to improve work-family compatibility. 145 publications were included in the overview. RESULTS: The available literature focuses on physicians and nursing staff while publications on other professions are largely lacking. The methodological quality of existing studies is mostly low, including a lack of meta-analyses. Several studies document dissatisfaction in physicians and nursing staff regarding reconciliation of work and family life. Only few intervention studies were found that seek to improve work-life compatibility; few of them focus on employees in healthcare. There are also deficits with respect to linking work-family issues with aspects of healthcare in rural areas. CONCLUSIONS: There is a shortage of systematic national and international research regarding work-family compatibility, especially when it comes to the evaluation of interventions. The overview provides starting points for improving work-family compatibility in healthcare.
EVALuna2:211666

Dementia patients in palliative care according to data from the German National Hospice and Palliative Care Register (2009–2021) - Donath, Carolin; Ostgathe, Christoph; Heckel, Maria (BMC Palliative Care, 2024)
Background: People with dementia are less in focus of palliative care research than other patient groups even though the awareness of their palliative and end-of-life care needs is rising. Empirical data analyses on people with dementia in palliative care services are lacking. Aim: To explore the prevalence of dementia diagnoses as per the ICD criteria among users of various palliative care settings and to compare use of palliative services, care pathways, and outcomes in people with and without a dementia diagnosis. Design: We conducted retrospective analysis of dementia diagnoses as per ICD (F00-F03/G30) in the German National Hospice and Palliative Care Register between 2009 and 2021. The analysis used methods of descriptive and inferential statistics, including the Bonferroni correction for alpha error inflation. Setting/participants: We limited the analysis to the subsample of people aged over 64. Results: The prevalence of dementia in the different settings of palliative care was lower than in the age-comparable population: Of the 69,116 data sets included in the analysis, a small minority (3.3%) was coded with dementia as the principal diagnosis. Among patients on inpatient palliative care wards, 0.8% (148 of 19,161) had a dementia diagnosis, as did 2.2% (52 of 2,380) of those under hospital palliative care support teams and 4.3% (2,014 of 46,803) of those receiving specialized palliative care at home. Conclusions: The records of the German National Hospice and Palliative Care Register suggest that the prevalence of dementia is lower than one might expect from general population data, though numbers are in line with international studies on proportion of dementia patients receiving palliative care. Future research could usefully examine whether this discrepancy stems either from omissions in coding dementia as patients’ principal diagnosis respectively from lapses in documentation of a dementia diagnosis previously made, or from barriers to accessing palliative care services or even displays being excluded from palliative care when trying to access it. Trial registration: No registration.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Clinical coding; Cognition disorders; Dementia; Documentation; Health services accessibility; Health Services Research; Palliative Care; Palliative Medicine

DemWG - Improving the Care of People with Dementia in outpatient assisted Living Communities - Donath, Carolin; Kratzer, André; Scheel, Jennifer Felicia; Schmidt, A.; Friedrich, A-C; Stiefler, S.; Wolf-Ostermann, K.; Grässel, Elmar (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Epidemiology of suicidal ideation, suicide attempts, and direct self-injurious behavior in adolescents with a migration background: a representative study - Donath, Carolin; Bergmann, Marie Christine; Kliem, Soeren; Hillemacher, Thomas; Baier, Dirk (BMC Pediatrics, 2019)
BackgroundData on the prevalence of suicidal ideation, suicide attempts, and direct self-injurious behavior in adolescents with a migration background are scarce. There are hints that this population is at risk. The aim of the study is to investigate the epidemiology of suicidal ideation, suicide attempts, and direct self-injurious behavior in adolescents with a migration background in Germany while taking gender-specific differences into consideration.MethodsA representative study with N=10,638 students (mean age 14.91years, SD=.73).) in the state of Lower Saxony in Germany was conducted. In the 2014-2015 school year, 672 classes were selected by randomly sampling different school types. The participation rate was 84.1%, excluding any classes for which the director refused to provide consent. A total of 49.8% were female adolescents, and 23.3% of the participants had a migration background. Target variables were assessed with items from the Ottawa Self-Injury Inventory, the Self-Harm Behavior Questionnaire and the Self-Harm Inventory, partly adapted.ResultsOf all students, 7.6% had a lifetime history of suicide attempts, and 36.6% answered with a rating of at least rarely when asked to rate the lifetime prevalence of suicidal ideation. The 12-month prevalence of direct self-injurious behavior was 17.8%. Adolescents with a migration background showed a significantly higher prevalence of all three constructs (p=.006; p<.001; p=.006). Male students with a migration background reported a significantly higher lifetime prevalence of suicide attempts (4.7% vs. 3.1%) than native males (p=.009). Female students with a migration background reported a significantly higher lifetime prevalence of suicide attempts (15.9% vs. 10.4%) and suicidal ideation (often 12.1% vs. 8.9%) than native female students (p<.001; p=.008).ConclusionOur assessment indicates an elevated risk for suicidal behaviors in adolescents with a migration background. From research on adults, it is known that the dominant motives for suicidal behavior in migrants are associated with their migration history/situation. As suggested by Cramer and Kapusta's (Front Psychol 8:1756, 2017) theoretical model, the Social-Ecological Framework of Theory, Assessment, and Prevention, there is a need for culturally sensitive preventions that take into account the specific reasons for suicide attempts in migrants.
CRIS-Team WoS Importer:2019-02-21

Evidence-based health services research–a short review and implications - Grässel, Elmar; Donath, Carolin; Hollederer, A.; Drexler, Hans; Kornhuber, Johannes; Zobel, A.; Kolominsky-Rabas, Peter (Gesundheitswesen, 2015)
Health services research aims to generate knowledge about care processes of people with illnesses who access health-care services. In addition, the consequences of those processes in the care routine concerning the involved persons and the health system are analyzed. CONCEPT OF THE THEORETICAL WORK: In the first part of the manuscript, an overview concerning the current definitions and subsumptions of the concept of health services research is given. The second part of the manuscript focuses on demonstrating how evidence-based health services research can be used to enable optimization of the care system. The concept is called the "circle of care optimization". In the first step the current care situation concerning its deficits and their reasons is analyzed. In the second step a relevant care goal is defined. In the third step an improvement of an existing care process is developed to achieve the defined care goal. In the fourth step, a comparative empirical study with a high-quality study design is carried out, to assess whether the improved care process is superior to the current care as usual. A health economic evaluation will be performed if applicable. If the results show no or only small advantages, the "circle" starts again with step 3. However, if the results show a significant effect in favour of the new care process and are relevant for the delivery of care and efficient in the context of health economics, a fifth step will be performed which involves developing and testing strategies for implementation. Where relevant, the consequences of implementation are investigated in a sixth step. A "best-practice" practical example is demonstrated to illustrate the "circle of care optimization".conclusions are derived by illustrating future challenges for health services research.
EVALuna2:9737

From board to bedside - training the communication competences of medical students with role plays - Luttenberger, Katharina; Grässel, Elmar; Simon, Cosima; Donath, Carolin (Bmc Medical Education, 2014)
Role plays and standardized patients are often used in medical education and have proven to be effective tools for enhancing the communication skills of medical students. Most course concepts need additional time and teaching staff, and there are only a few studies about role plays in the preclinical segment.We developed a highly consolidated concept for the curricular course of 2nd-year medical students, including ten role plays about five subjects: anamnesis, shared decision making, prevention, breaking bad news, and so-called "difficult interactions". Before the course, all students were asked about their expectations and attitudes toward the course. After the course, all students rated the course, their individual learning progress, whether their expectations had been fulfilled, and re-evaluated their attitudes. Questionnaires were self-report measures and had a quantitative and a short qualitative section and were analyzed with descriptive statistics. Group differences (sex, age, role played) were evaluated with t tests at a Bonferonni-corrected significance level of p = .03 and the non-parametric U-tests.Implementing this practical course concept is possible without incurring additional costs. This paper not only shows how that can be done but also provides 5 examples of role scripts for different training subjects. The course concept was highly appreciated by the students. More than 75% felt that they had learned important communication techniques and would be better able to handle difficult situations. Playing the doctor's role was felt to be more useful than playing the patient's role. Women admitted a higher degree of shyness in the beginning and gave higher ratings to their learning progress than men. Students' most frequent wish in the qualitative analysis was to be able to play the doctor's role at least once. The students' answers showed a differentiated pattern, thus suggesting that the influence of social desirability was minimal.Practical skills can be taught successfully in the preclinical stage of medical education even without an increase in resources. The course concept described in this article provides an effective means by which to do so.
EVALuna2:23626

Immediate Intervention Effects of Standardized Multicomponent Group Interventions on People with Cognitive Impairment: A Systematic Review - Özbe, Dominik; Grässel, Elmar; Donath, Carolin; Pendergrass, Anna (Journal of Alzheimer's Disease, 2019)
Background: There is no curative medical treatment for dementia. Therefore, researchers turned their attention to nonpharmacological treatment approaches. Many reviews analyzed the efficacy of single-component interventions, but there has been no systematic review of multicomponent interventions so far.
CRIS-Team WoS Importer:2019-02-22

Implementation and Effect of the Multimodal Psychosocial MAKS Intervention in Day Care Centers for People with Cognitive Impairment: Follow-up Results After the End of the RCT - Grässel, Elmar; Donath, Carolin; Pendergrass, Anna; Luttenberger, Katharina (Gesundheitswesen, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-11-12

Is Binge Drinking also an Issue in Adulthood? - A Representative Study - Donath, Carolin (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Is parenting style a predictor of suicide attempts in a representative sample of adolescents? - Donath, Carolin; Grässel, Elmar; Baier, Dirk; Bleich, Stefan; Hillemacher, Thomas (BMC Pediatrics, 2014)
Suicidal ideation and suicide attempts are serious but not rare conditions in adolescents. However, there are several research and practical suicide-prevention initiatives that discuss the possibility of preventing serious self-harm. Profound knowledge about risk and protective factors is therefore necessary. The aim of this study is a) to clarify the role of parenting behavior and parenting styles in adolescents' suicide attempts and b) to identify other statistically significant and clinically relevant risk and protective factors for suicide attempts in a representative sample of German adolescents.In the years 2007/2008, a representative written survey of N = 44,610 students in the 9th grade of different school types in Germany was conducted. In this survey, the lifetime prevalence of suicide attempts was investigated as well as potential predictors including parenting behavior. A three-step statistical analysis was carried out: I) As basic model, the association between parenting and suicide attempts was explored via binary logistic regression controlled for age and sex. II) The predictive values of 13 additional potential risk/protective factors were analyzed with single binary logistic regression analyses for each predictor alone. Non-significant predictors were excluded in Step III. III) In a multivariate binary logistic regression analysis, all significant predictor variables from Step II and the parenting styles were included after testing for multicollinearity.Three parental variables showed a relevant association with suicide attempts in adolescents - (all protective): mother's warmth and father's warmth in childhood and mother's control in adolescence (Step I). In the full model (Step III), Authoritative parenting (protective: OR: .79) and Rejecting-Neglecting parenting (risk: OR: 1.63) were identified as significant predictors (p < .001) for suicidal attempts. Seven further variables were interpreted to be statistically significant and clinically relevant: ADHD, female sex, smoking, Binge Drinking, absenteeism/truancy, migration background, and parental separation events.Parenting style does matter. While children of Authoritative parents profit, children of Rejecting-Neglecting parents are put at risk - as we were able to show for suicide attempts in adolescence. Some of the identified risk factors contribute new knowledge and potential areas of intervention for special groups such as migrants or children diagnosed with ADHD.
EVALuna2:23618

Manchmal trink ich auch Wasser… – Alkoholkonsum von Menschen mit leichter kognitiver Beeinträchtigung - Donath, Carolin; Grässel, Elmar; Scheuermann, Julia-Sophia; Bösl, Sophia; Scheerbaum, Petra (Psychiatrische Praxis, 2023)
Aim Risky alcohol consumption increases the risk of dementia for people with mild cognitive impairment (MCI). The aim of this study is to assess alcohol consumption in people with MCI. Methods Socio-demographics, 12-month prevalence, 30-d prevalence, prevalence of risky consumption ( > 10 g/20 g/d pure alcohol for women/men) and binge drinking (≥ 50 g pure alcohol on one occasion) were recorded in 270 people (≥ 60 years) with MCI from the German RCT "Brainfit-Nutrition" in 2022. Results Approximately half of the people with MCI (50.8 %) drink at least once a week. About one fifth (17.0 %) of participants met the criterion for binge drinking; every third woman (34.8 %) and every fifth man (18.6 %) crossed the line to risky consumption in the last 30 d. Discussion Generally, people with MCI show similar consumption prevalence as the 65 + German general population. However, the prevalence of risky consumption in women with MCI is significantly higher.
CRIS-Team Scopus Importer:2023-09-22
Keywords: alcohol abstinence; alcohol drinking; binge drinking; cognitive dysfunction; sociodemographic factors

Prävalenz und Prädiktoren für Rauschtrinken – Querschnittsbefragung repräsentativ für Niedersachsen - Donath, Carolin; Sack, Carolin; Pendergrass, Anna; Weiss, Maren; Baier, Dirk (Sucht, 2019)

Predictors of falls and hospital admissions in people with cognitive impairment in day-care: role of multimorbidity, polypharmacy, and potentially inappropriate medication - Scheel, Jennifer; Luttenberger, Katharina; Grässel, Elmar; Kratzer, André; Donath, Carolin (BMC Geriatrics, 2022)
Background Multimorbidity, polypharmacy, and potentially inappropriate medication (PIM) pose challenges for the care of people with cognitive impairment. The aim of the present study is to explore whether multimorbidity, polypharmacy, and PIM predict falls and hospital admissions in a sample of people with cognitive impairment in day-care centers in Germany. Methods We used data from the German day-care study (multicenter longitudinal study, n = 433). Multimorbidity was defined as >= 2 chronic diseases. Polypharmacy was defined as prescriptions to >= 5 drugs. Potentially inappropriate medication was defined as scoring on the PRISCUS list. Binary logistic regression analyses were computed to determine whether multimorbidity, polypharmacy, and potentially inappropriate medication at t0 predicted falls and hospital admissions as outcomes at t1 (six months later). Results The rate of multimorbidity and polypharmacy was 87.8% and 60.3%, respectively. 15.9% of the people with cognitive impairment received PIM / PRISCUS-listed drugs, 43.6% ACB-listed drugs, and 52.7% CNS depressant drugs. Falls and hospital admissions during follow-up were prevalent in 19.4% and 24.7% of the people with cognitive impairment. Both were significantly predicted by the total number of drugs (falls: OR = 1.152, p = 0.001, overall model: p < 0.001; hospital admissions: OR = 1.103, p = 0.020, overall model: p = 0.001), even if regression analyses were controlled for the number of comorbidities. Conclusions Polypharmacy and potentially inappropriate medication are highly prevalent in people with cognitive impairment in German day-care centers. The number of drugs and appropriateness of medication seem to be crucial for the risk of falls and hospital admissions. Polypharmacy and PIM should be critically reviewed by healthcare providers and avoided as much as and whenever possible.
CRIS-Team WoS Importer:2022-08-26

Predictors of intensity of use of adult day care centers in people with cognitive impairment - Wasic, Catharina; Grässel, Elmar; Luttenberger, Katharina; Donath, Carolin (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background Adult day care is an established concept in Germany for people with cognitive impairment; however, only a small fraction of people in need for care actually use adult day care. Studies so far highlighted some predictors for the use of adult day care; however, it remains unclear which factors are associated with the intensity of use. Objective To identify relevant predictors for the intensity of use of adult day care using the Andersen healthcare utilization model. Material and methods Data used were obtained within the project dementia in day care with psychosocial MAKS interventions (DeTaMAKS), which studied adult day care users with cognitive impairments and their family caregivers. A logistic regression was performed to predict frequent or low use of adult day care. Results The following factors were significantly associated with higher intensity of use: civil status of adult care user being widowed or single, higher educational level of caregiver, higher care level, longer duration of adult day care use and more mental and behavioral symptoms of the adult day care user. The sensitivity analysis for cohabiting dyads additionally showed a higher intensity of use with a lower age of the caregiver and shorter distance between place of residence and adult day care but not with respect to educational level of the caregiver and mental and behavioral symptoms of the user. Conclusion The results show a need for adult day care, which increases with caregivers being employed and users living outside of permanent relationships. A short distance to the adult care center as well as flexible care options may increase the frequency of use.
CRIS-Team WoS Importer:2021-10-08

Psychopharmakologische Behandlung von Menschen mit schwerer Demenz - Diehl, Kristina; Kratzer, André; Donath, Carolin; Maas, Renke; Fromm, Martin; Kornhuber, Johannes; Grässel, Elmar (Deutsches Ärzteblatt international, 2022)
CRIS-Team Scopus Importer:2022-11-25

Reasons for hospitalization of people with dementia-A scoping review - Stiefler, Susanne; Dunker, Ellen; Schmidt, Annika; Friedrich, Anna-Carina; Donath, Carolin; Wolf-Ostermann, Karin (Zeitschrift für Gerontologie und Geriatrie, 2022)
Background Hospitalization represents a high burden for people with dementia, which can accelerate the decline of cognitive and motor skills. Behavioral changes and orientation problems may be increased in people with dementia during hospitalization. Some hospitalizations are potentially preventable by improved outpatient care. Objective To provide an up to date overview of the most common reasons for hospitalization of people with dementia or mild cognitive impairment. Material and methods A systematic literature search was conducted in the databases PubMed (R), CINAHL and PsycINFO (R) in May 2020 to conduct the scoping review. Studies in German and English published between July 2010 and May 2020 were included. Results The most common reasons for hospitalization, which were named in the 14 included studies, were infectious diseases, especially respiratory infections and urinary tract infections, cardiovascular diseases (in general or specific, e.g. heart failure) and injuries, poisoning, fractures and falls, and gastrointestinal diseases. Conclusion Most of the most common reasons for hospitalization are ambulatory care-sensitive hospital cases. Strengthening outpatient care for people with dementia may help prevent hospitalizations.
CRIS-Team WoS Importer:2022-04-29

Responder Analysis of a Multicomponent Non-Pharmacological Intervention (MAKS) for People With Cognitive Impairment in the German Day-Care Study (DeTaMAKS) - Luttenberger, Katharina; Grässel, Elmar; Behrndt, Elisa-Marie; Özbe, Dominik; Donath, Carolin; Scheel, Jennifer Felicia (Frontiers in Psychiatry, 2019)
Background: Multicomponent non-pharmacological therapies have been shown to be effective at reducing cognitive symptoms and slowing deterioration in abilities to perform activities of daily living (ADL) in individuals with cognitive impairment. However, little is known about response rates and predictors of response.
CRIS-Team WoS Importer:2019-09-06

RISK REDUCTION OF HOSPITAL ADMISSIONS FOR PEOPLE WITH DEMENTIA IN SHARED-HOUSING ARRANGEMENTS: THE DEMWG STUDY - Wolf-Ostermann, Karin; Stiefler, Susanne; Schmidt, Annika; Friedrich, Anna-Carina; Grässel, Elmar; Donath, Carolin; Scheel, Jennifer; Kratzer, André (INNOVATION IN AGING, 2022)
CRIS-Team WoS Importer:2023-03-10

Searching for success: Development of a combined patient-reported-outcome ("PRO") criterion for operationalizing success in multi-modal pain therapy - Donath, Carolin; Dorscht, Lisa; Grässel, Elmar; Sittl, Reinhard; Schoen, Christoph (BMC Health Services Research, 2015)
There is a need for a way to measure success in multi-modal pain therapy that researchers and clinicians can agree upon. According to developments in health services research, operationalizing success should take patient-reported outcomes into account. We will present a success criterion for pain therapy that combines different patient-reported variables and includes validity measures. The usable criterion should be part of a statistically significant and satisfactory model identifying predictors of successful pain therapy.Routine data from 375 patients treated with multi-modal pain therapy from 2008 to 2013 were used. The change scores of five constructs were used for the combined success criterion: pain severity, disability due to pain, depressiveness, and physical- and mental-health-related quality of life. According to the literature, an improvement of at least ½ standard deviation was required on at least four of the five constructs to count as successful. A three-step analytical approach including multiple binary logistic regression analysis was chosen to identify the predictors of therapy success with the success criterion as the dependent variable.A total of 58.1% of the patients were classified as successful. Convergent and predictive validity data show significant correlations between the criterion and established instruments, while discriminative validity could also be shown. A multiple binary logistic regression analysis confirmed the feasibility; a significant model (Chi(2) (8) = 52.585; p < .001) that explained 17.6% of the variance identified the following predictors of therapy success: highest pain severity in the last 4 weeks, disability due to pain, and number of physician visits in the last 6 months.It is possible to develop a feasible success criterion that combines several variables and includes patient-reported outcomes ("PROs") with routine data that can be used in a predictor analysis in multi-modal pain therapy. The criterion was based on basic constructs used in pain therapy and used widespread validated self-rating instruments. Thus, it should be easy to transfer this criterion to other institutions.
EVALuna2:16678

Subjective Distress and Depression in Relatives of People with cognitive Impairments - Long-term Results of the DeTaMAKS Study (RCT) - Donath, Carolin; Luttenberger, Katharina; Grässel, Elmar (GESUNDHEITSWESEN, 2021)
CRIS-Team WoS Importer:2022-05-20

Substance consumption in adolescents with and without an immigration background: a representative study-What part of an immigration background is protective against binge drinking? - Donath, Carolin; Baier, Dirk; Grässel, Elmar; Hillemacher, Thomas (BMC Public Health, 2016)
Representative data indicate that adolescents with an immigration background show less harmful patterns of consumption, for example, they practice binge drinking less often. It remains to be shown whether this also applies to substances such as tobacco and cannabis and if the "healthier" patterns of consumption are permanent or if they gradually disappear as the level of integration increases. Using representative data, the current study was designed to a) present the epidemiology of the consumption of alcohol, tobacco, and cannabis of adolescents with and without an immigration background in 2013 and b) to analyze which immigration-specific variables predict problematic alcohol consumption in adolescents with an immigration background.A representative, written survey was administered to 9512 students in the 9th grade from Lower Saxony, Germany in 2013 by the "Kriminologisches Forschungsinstitut Niedersachsen (KfN)." Data were collected from 1763 adolescents with an immigration background regarding their cultural, structural, social, and identificative integration. These variables were introduced as predictors in a multiple logistic regression analysis with binge drinking during the last 30 days as the dependent variable.Compared with German adolescents without an immigration background, significantly fewer adolescents with an immigration background had already tried alcohol, but they were significantly more likely to report experience with cigarettes and cannabis. In the group of adolescents with an immigration background, the percentage of binge drinkers fluctuated by country of origin (p < .001). In the regression model, binge drinking was associated with a lower targeted school leaving certificate (p < .001), not living on social welfare (p = .038), and the strong assimilation (p = .015) of the adolescent. Binge drinking was negatively associated with attitudes that favored segregation (p < .001) and a stronger attachment of the parents to the traditions of their country of origin (p = .003).It cannot be confirmed that adolescents with an immigration background generally show less harmful patterns of consumption. Distinctions have to be made regarding the substance, the adolescent's country of origin, and the level of assimilation or segregation of the adolescent and his/her family.
EVALuna2:23784

The DemWG study: reducing the risk of hospitalisation through a complex intervention for people with dementia and mild cognitive impairment (MCI) in German shared-housing arrangements: study protocol of a prospective, mixed-methods, multicentre, cluster-randomised controlled trial - Kratzer, André; Scheel, Jennifer; Wolf-Ostermann, Karin; Schmidt, Annika; Ratz, Katrin; Donath, Carolin; Grässel, Elmar (BMJ Open, 2020)
INTRODUCTION: Shared-housing arrangements (SHAs) are small, home-like care environments in Germany. Residents are predominantly people with dementia. The risk for all-cause hospitalisation is consistently higher for people with dementia compared with people without dementia and there is currently no evidence-based intervention to reduce the risk of hospitalisation. Thus, the DemWG study investigates whether a complex intervention is effective in reducing hospitalisation (primary outcome), behavioural and psychological symptoms of dementia and falls and for stabilising cognitive functioning and quality of life in people with dementia and mild cognitive impairment (MCI) in German SHAs. METHODS AND ANALYSIS: Based on the UK Medical Research Council framework 'Developing and evaluating complex interventions', a prospective, mixed-methods, multicentre, cluster-randomised controlled trial combining primary and secondary data analyses as well as quantitative and qualitative research methods is being conducted. The intervention consists of three parts: (A) education of nursing staff in SHAs; (B) awareness raising and continuing medical education (CME) of general practitioners; (C) multicomponent non-pharmacological group intervention MAKS-mk+ ('m'=motor training; 'k'=cognitive training; '+'=fall prevention) for people with dementia and MCI. Randomisation is stratified by the German federal states and type of setting (rural vs urban). Neither the trained professionals nor the participants are blinded. Data are collected at baseline and after 6, 12 and 18 months with standardised instruments. Quantitative data will be analysed by multivariate analyses according to the general linear model, qualitative data using qualitative content analysis. Recruitment is still ongoing until 31 December 2020. ETHICS AND DISSEMINATION: All procedures were approved by the Ethics Committee of the University of Bremen (Ref. 2019-18-06-3). Informed consent will be obtained before enrolment of participants. Due to findings of previous randomised controlled trials, serious adverse events are not expected. Results will be disseminated in peer-reviewed journal publications and conference presentations. TRIAL REGISTRATION NUMBER: ISRCTN89825211.
CRIS-Team Scopus Importer:2020-12-11
Keywords: delirium & cognitive disorders; dementia; geriatric medicine

Treating depression in an outpatient setting: Predictors of patient response to bouldering psychotherapy, cognitive behavioural therapy or exercise alone - Luttenberger, Katharina; Donath, Carolin; Grässel, Elmar; Kornhuber, Johannes; Schlüter, Annika; Dorscht, Lisa; Kind, Leona (Clinical Psychology & Psychotherapy, 2023)
Background: Bouldering psychotherapy (BPT) for depression has proven effective, but nothing is known about its potential predictors of response. This study should identify predictors of response to BPT, cognitive behavioural therapy (CBT) and an active control (home-based exercise programme; EP) using a literature-based model. Methods: In a multicentre randomised controlled trial, 233 outpatients were assigned to BPT, CBT or EP. Response (reduction of at least 46% on the Montgomery–Åsberg Depression Rating Scale [MADRS]) and remission (≤7 MADRS points) were defined as suggested by the literature. Predictors of response were identified twofold: (1) univariate analyses followed by logistic regression analyses in each group with all predictors yielding a univariate p-value <.20 and (2) a backward regression analysis with all potential predictors. Only variables that emerged as predictors in both types of analyses were interpreted. Results: There was a significantly greater proportion of responders (p =.035) in the BPT than in the EP. The chance of response in the BPT was higher for patients with a higher health-related quality of life. In the EP, response was higher for patients with lower interpersonal sensitivity, suffering from their first episode and living with a partner. Conclusions: Response rates in BPT are similar to or even higher than in other outpatient psychotherapy group therapies. BPT and CBT are suitable for a wide range of patients, but patients with higher functionality could start with psychoeducation and exercise.
CRIS-Team Scopus Importer:2023-09-15
Keywords: bouldering; cognitive behavioural therapy; depression; exercise; group psychotherapy; psychotherapy

Validation of a core patient-reported-outcome measure set for operationalizing success in multimodal pain therapy: useful for depicting long-term success? - Donath, Carolin; Geiss, Christa; Schoen, Christoph (BMC Health Services Research, 2018)
BACKGROUND: The study aims to validate a previously developed and published combined success criterion for patients after multimodal pain therapy (Donath et al., BMC Health Serv Res 15:272, 2015). The criterion classifies treated patients as successful in the long term on the basis of pain severity, disability through pain, depressiveness, and health-related quality of life. METHODS: Routine longitudinal data of 135 pain patients treated with multimodal pain therapy in 2014-2015 at the Interdisciplinary Pain Center of the University Clinic Erlangen were available at baseline, therapy start, therapy end, and 12 months after treatment. Patients were, on average, 51.0 (SD 11.1) years old and to 63.7% female, two thirds were employed (66.7%). We conducted an analysis of concurrent validity (with: pain severity, disability through pain, depressiveness, mental and physical quality of life), criterion validity (with disability days, self-rated success), convergent validity (with stress, anxiety, well-being), and discriminant validity (with chronicity of pain, comorbidity), objectivity, and reliability. Statistically, descriptive and inference statistics, graphical methods and MANOVAs were used. RESULTS: Patients classified as successful had significantly better values on the 5 variables demonstrating concurrent validity (all p < .001), significantly fewer Disability days (M = 15.31 (SD = 23.15) vs. M = 26.75 (SD = 29.15)); t (133) = 2.308; p = .024, less Anxiety (Pillai-Spur: F (3, 131) = 2.972, p = .034), less Stress (Pillai-Spur: F (3, 131) = 9.907, p < .001), and better Well-being (Pillai-Spur: F (3, 131) = 9.594, p < .001) 12 months after treatment than patients classified as not successful. The Spearman correlation between success classification and Chronicity stage was .094 (p = .280). CONCLUSION: We demonstrated the validity of the combined success criterion with long-term data in addition to confirming the reliability and objectivity of the criterion. Future research might consider identifying predictors of success in multi-modal pain therapy.
EVALuna2:211700

Validation of the German version of the state mindfulness scale for physical activity in a clinical sample - Wallner, Jan; Kind, Leona; Donath, Carolin; Kornhuber, Johannes; Luttenberger, Katharina (Journal of Patient-Reported Outcomes, 2024)
Background: Mindfulness has been studied as a treatment option for a large range of psychological disorders and is associated with a multitude of positive psychological outcomes. There are now several scales for measuring mindfulness as both a trait and a state. As mindfulness potentially plays a critical role in maintaining physical activity habits, the State Mindfulness Scale for Physical Activity (SMS-PA) was developed to specifically measure mindfulness in a physical activity context. This study aimed to provide validity evidence for a German version of the SMS-PA (henceforth called SMS-PA-G) in a clinical sample. Methods: We used baseline data from 129 participants in the randomised controlled trial ‘New Ways to Cope with Depression’. The sample, which was screened for clinical depression symptoms, completed the SMS-PA-G and several other psychometric scales for capturing state mindfulness, self-efficacy, sense of coherence, anxiety, depression, and physical activity. We conducted reliability and item analyses and ran a confirmatory factor analysis. Also, we assessed construct validity through correlations with the abovementioned scales and through differences in SMS-PA scores between physically active and nonactive participants. Results: The mean SMS-PA-G score in our sample was 25.3 with a standard deviation of 8.5. The item and reliability analyses provided satisfactory Cronbach’s alpha and discriminatory power values. The confirmatory factor analysis showed that physical activity mindfulness can best be described via a bifactor model, with specific mind and body factors and a general mindfulness factor. We found the expected relationships with the attention subscale of state mindfulness, self-efficacy, and sense of coherence but did not find them with the awareness subscale of state mindfulness, depression, and anxiety. As hypothesised, physically active participants exhibited higher SMS-PA-G values than nonactive participants. Conclusions: The SMS-PA-G is an internally consistent test instrument that captures respondents’ general physical activity mindfulness and their attention to mental and bodily events. Whereas validity evidence was generally supportive of the SMS-PA-G, its relationships with other constructs require further investigation. Trial registration: ISRCTN, ISRCTN12347878. Registered 28 March 2022, https://www.isrctn.com/ISRCTN12347878.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Exercise; German; Mindfulness; Physical activity; State; Validation

Vitamin B-Can it prevent cognitive decline? A systematic review and meta-analysis - Behrens, Annika; Grässel, Elmar; Pendergrass, Anna; Donath, Carolin (Systematic Reviews, 2020)
BACKGROUND: Development of cognitive decline represents substantial issues in today's society, steadily gaining importance with increasing life expectancy. One potential approach to preventing cognitive decline is to lower homocysteine by administering vitamin B. In this systematic review and meta-analysis, we address this topic and investigate whether oral supplementation of vitamin B can successfully prevent cognitive decline in cognitively unimpaired individuals. METHODS: A computerized systematic literature search was conducted using the electronic databases PubMed, Embase, and the Cochrane Library. Eligibility criteria included oral supplementation with vitamin B (B1, B6, folic acid, and B12) and the absence of cognitive impairment. A meta-analysis was conducted with "global cognition" as the primary outcome of this review. Secondary outcomes were changes in cognitive function in other cognitive domains reported in the included studies. Risk of bias was assessed according to the Cochrane Risk of Bias tool and the GRADE approach to establish the overall certainty of the evidence. RESULTS: The meta-analysis did not yield a significant overall effect of supplementation with vitamin B on cognitive function (Z = 0.87; p = 0.39; SMD, 0.02; 95% CI, - 0.034, 0.08). A sensitivity analysis focusing on specific risk factors did not alter this result. Some studies reported isolated significant effects of the intervention on secondary outcomes. However, these findings were outnumbered by the number of cognitive tests that did not yield significant effects. DISCUSSION: We found no overall evidence that oral vitamin B supplementation prevented cognitive decline. The isolated significant effects that were reported could be attributed to methodological issues. The results of this review do not provide evidence that population groups with certain risk factors would profit more from the intervention than others. Our findings do not apply to forms of administration other than oral supplementation nor do they offer information regarding the treatment of cognitively impaired individuals via the administration of vitamin B. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42017071692.
CRIS-Team Scopus Importer:2020-05-29
Keywords: Cognition[Mesh]; Dementia[Mesh]; Folic Acid[Mesh]; Prevention; Vitamin B12[Mesh]; Vitamin B6[Mesh]

What helps, what hinders?—Focus group findings on barriers and facilitators for mobile service robot use in a psychosocial group therapy for people with dementia - Wasic, Catharina; Erzgräber, Robert; Unger-Büttner, Manja; Donath, Carolin; Böhme, Hans Joachim; Grässel, Elmar (Frontiers in Robotics and AI, 2024)
Introduction: Many countries are facing a shortage of healthcare workers. Furthermore, healthcare workers are experiencing many stressors, resulting in psychological issues, impaired health, and increased intentions to leave the workplace. In recent years, different technologies have been implemented to lighten workload on healthcare workers, such as electronic patient files. Robotic solutions are still rather uncommon. To help with acceptance and actual use of robots their functionalities should correspond to the users’ needs. Method: In the pilot study Care4All–Initial, we developed and field-tested applications for a mobile service robot in a psychosocial, multimodal group therapy for people with dementia. To guide the process and assess possible facilitators and barriers, we conducted a reoccurring focus group including people with dementia, therapists, professional caregivers as well as researchers from different disciplines with a user-centered design approach. The focus group suggested and reviewed applications and discussed ethical implications. We recorded the focus group discussions in writing and used content analysis. Results: The focus group discussed 15 different topics regarding ethical concerns that we used as a framework for the research project: Ethical facilitators were respect for the autonomy of the people with dementia and their proxies regarding participating and data sharing. Furthermore, the robot had to be useful for the therapists and attendees. Ethical barriers were the deception and possible harm of the people with dementia or therapists. The focus group suggested 32 different applications. We implemented 13 applications that centered on the robot interacting with the people with dementia and lightening the workload off the therapists. The implemented applications were facilitated through utilizing existing hard- and software and building on applications. Barriers to implementation were due to hardware, software, or applications not fitting the scope of the project. Discussion: To prevent barriers of robot employment in a group therapy for people with dementia, the robot’s applications have to be developed sufficiently for a flawless and safe use, the use of the robot should not cause irritation or agitation, but rather be meaningful and useful to its users. To facilitate the development sufficient time, money, expertise and planning is essential.
CRIS-Team Scopus Importer:2024-07-12
Keywords: dementia; focus group; institutional care; robot-assisted therapy; user-centered design

Wirkung von Sportinterventionen auf die psychische Gesundheit von Jugendlichen: Ein systematisches Review mit Praxisbeispiel Boulderpsychotherapie - Donath, Carolin; Atzmüller, Lukas; Florack, Jakob; Engel, Caroline; Luttenberger, Katharina (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2024)
The Effect of Exercise Therapy on Adolescent Mental Health: A Systematic Review with Practical Example Abstract: The mental health of children and adolescents in Germany is currently highly burdened. Because of the psychotherapeutic care situation, easily accessible, less stigmatizing, and efficient offers are urgently needed. Exercise therapy would be one possibility. However, the effectiveness of such offers must first be proven. We conducted a systematic review concerning the effectiveness of exercise therapy on the mental health of children and adolescents which included studies since 2020 (subsequent to Hale et al., 2021). We analyzed a total of 17 intervention studies based on the PRISMA statement. The results show that exercise therapy interventions significantly affect certain populations: Attention and cognitive skills significantly improved in children and adolescents with ADHD; for depression, we found positive effects for affection. Some studies revealed significant effects across populations on the quality of life and sleep. In children and adolescents with autism or learning disabilities, we found positive effects on social behavior. Thus, according to the literature, exercise therapy is a recommendable therapy option for children and adolescents with mental health problems. As an illustration, we present a boulder intervention as a combined exercise intervention and psychotherapy along with its feasibility as a possible practical example.
EVALuna2:555726